Development of Micro Hydro Power Plant Prototype as A Field Laboratory for Educational and Research Purposes - Yanuar Zulardiansyah, Arief; Mohamad Fahmi, Abdul Rahim; Naemah, Mubarakah; Mohd Hafiez Izzwan, Saad; Hamzah, Eteruddin (IEEE, 2021)
The need for cheaper electricity generation rises as the price of fossil fuels is increasingly nowadays. Hydropower plant is one of the most efficient and environmentally friendly alternative power plant sources. In this research works, a prototype of small-scale hydro power plant known as micro hydro power plant (MHPP) was developed for educational and research purpose. The motivation of this work is based on there is no field laboratory could be used for students to study the concept and actively involved in electricity generation at Universiti Teknologi Malaysia (UTM) Johor Bahru campus, Malaysia. This work hopefully become the catalyst for further research regarding renewable energy source, particularly in MHPP research. The research flow for this work begins with feasibility activities to determine some potential sites for development of MHPP at UTM Johor Campus. There are 7 (seven) potential sites based on site visits and data analysis. From the data analysis, the most suitable site chosen for MPPP prototype development. The prototype was built based on the improved design. The results show that the constructed prototype is capable for generating electricity. This prototype can be used as a field laboratory and for educational and research purpose.